Environmental Pollutants and Biodiversity Loss: Analyzing the Role of Persistent Organic Pollutants in Ecosystem Decline - Sudipta Roy (International Journal of Toxins and Toxics, 2024)
Persistent Organic Pollutants (POPs) significantly impact biodiversity, with various factors influencing their effects on species and ecosystems. Species in poor body condition, like carnivores and predators, are more vulnerable to POPs due to weakened immune systems and reduced detoxification abilities. Dietary habits also affect the accumulation of POPs, as chemicals biomagnify up the food chain. Carnivores accumulate higher concentrations, leading to reproductive failures, hormonal imbalances, and death, while herbivores face lower risks. Age plays a role, with juveniles more vulnerable to developmental defects, while older animals can better metabolize pollutants. Sex differences are notable, with females often more affected by pollutants disrupting reproductive health. Migratory species, such as birds and marine mammals, accumulate POPs during migration, and the added stress of migration exacerbates the negative effects. Furthermore, POPs induce epigenetic changes, which alter gene expression without changing the DNA sequence. These modifications can lead to neurodevelopmental disorders in both humans (e.g., ADHD, autism, cognitive impairments) and wildlife (e.g., impaired brain function, reduced reproduction). Epigenetic disruptions in wildlife can affect survival, behavior, and reproduction, leading to population declines and biodiversity loss. These changes can be passed down to offspring, compounding the effects over generations. Mitigating POP impacts requires reducing emissions, conducting research, and restoring ecosystems through coordinated conservation efforts, policy changes, and stronger regulations to protect human and environmental health.
Keywords: Biodiversity loss; Biomagnification; Conservation efforts; Epigenetic changes; Persistent Organic Pollutants (POPs)